Influence of the nutrient concentrations of whey on ethanol and biomass production and COD reduction - Murari, Cleidiane Samara [UNESP]; Moraes Niz da Silva, Debora Cristina [UNESP]; Silva, Bruna Lima da [UNESP]; Del Bianchi, Vanildo Luiz [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2017)
The present study aimed at the use of cheese whey as substrate for ethanol production by Kluyveromyces marxianus. The effect of the initial cheese whey concentration (M1 57.60; M2 45.60; M3 32.50 and M4 18.80 g L-1) on the alcoholic fermentation was studied. After sterilization, the in natura media were incubated at 30 degrees C for 48 hours, and then lactose, protein, ethanol, cell growth and chemical oxygen demand were analyzed. According to the results, M1 medium (the highest concentration) showed a greater production and volumetric productivity of ethanol 16.90 and 1.26 g L-1 hour(-1), respectively, and resulted in the greatest cell production and volumetric productivity of 5.80 and 0.40 g L-1 hour(-1), respectively. However, in terms of ethanol yield, the most satisfactory result was obtained using the M3 medium, pro 82.30% in 12 hours of fermentation. With respect to the COD, the organic substance content of M4 medium was reduced by 82.28%.
Keywords: bioprocess; biofuel; Kluyveromyces marxianus; environment